Interdisciplinary Management of Complex Regional Pain Syndrome of the Face. Issue 7 (1st July 2016) - Parkitny, Luke; Wand, Benedict Martin; Graham, Carl; Quintner, John; Moseley, G. Lorimer
Abstract: Background and Purpose: Orofacial pain disorders are relatively uncommon and pose a substantial diagnostic challenge. This case report documents the diagnosis and management of hemifacial pain in a patient who was referred to an interdisciplinary pain medicine unit. The purpose of this case report is twofold. First, it presents complex regional pain syndrome (CRPS) as a potential differential diagnosis in cases of facial pain. Second, it describes the successful adaption of contemporary management approaches for distal-extremity CRPS to treat people with CRPS of the facial region. Case Description: The patient had hemifacial pain and concomitant motor and autonomic symptoms after a small laceration of the eyelid. Extensive specialist medical evaluations were undertaken to exclude an underlying structural pathology. After detailed clinical assessments by a physical therapist, pain physician, and clinical psychologist, a diagnosis of CRPS involving the face was made. Outcomes: The patient's pain was largely unresponsive to pharmacological agents. A modified graded motor imagery program, together with desensitization and discrimination training, was commenced by the physical therapist and clinical psychologist. A positive clinical response was indicated by a decrease in allodynia, normalization of motor control, and regained function in activities of daily living. Discussion: Complex regional pain syndrome is an infrequently reported differential diagnosis that can be considered in patients with persistent facial pain. This case report highlights how careful examination and clinical decision making led to the use of an innovative therapeutic strategy to manage a challenging condition.